2022
DOI: 10.1111/tpj.15886
|View full text |Cite
|
Sign up to set email alerts
|

Effects of homoeologous exchange on gene expression and alternative splicing in a newly formed allotetraploid wheat

Abstract: SUMMARY Homoeologous exchange (HE) is a major mechanism generating post‐polyploidization genetic variation with important evolutionary consequences. However, the direct impacts of HE on gene expression and transcript diversity in allopolyploids without the intertwined evolutionary processes remain to be fully understood. Here, we analyzed high‐throughput RNA‐seq data of young leaves from plant groups of a synthetic allotetraploid wheat (AADD), which contained variable numbers of HEs. We aimed to investigate if… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 74 publications
3
5
0
Order By: Relevance
“…Lloyd et al (2018) found when homoeologous gene pairs have unequal expression, altering the ratio of homoeologous copies does not accurately compensate to maintain the same level of combined homoeolog expression. Similar results have since been observed in tetraploid wheat lines (Zhang et al 2022). Therefore, in the presence of unequal homoeolog expression, HEs will alter the stoichiometry of gene products for a homoeologous pair and would be predicted by the Gene Balance Hypothesis to be under selective constraint to maintain gene dosage balance.…”
Section: Introductionsupporting
confidence: 87%
“…Lloyd et al (2018) found when homoeologous gene pairs have unequal expression, altering the ratio of homoeologous copies does not accurately compensate to maintain the same level of combined homoeolog expression. Similar results have since been observed in tetraploid wheat lines (Zhang et al 2022). Therefore, in the presence of unequal homoeolog expression, HEs will alter the stoichiometry of gene products for a homoeologous pair and would be predicted by the Gene Balance Hypothesis to be under selective constraint to maintain gene dosage balance.…”
Section: Introductionsupporting
confidence: 87%
“…Moreover, natural allopolyploid species usually possess fully stabilized karyotypes, and hence, there is no real ‘control’ for comparison. By contrast, synthetic allopolyploids are model systems to assess the direct effects and immediate biological consequences of allopolyploidization‐incurred genome shock (Ramsey & Schemske, 2002; Xiong et al ., 2011; Gaebelein et al ., 2019; Ferreira de Carvalho et al ., 2021; Shimizu, 2022; Zhang et al ., 2022). This is because evolution is yet to happen in synthetic allopolyploids, and the same population contains both karyotypically variable and invariable individuals for straightforward comparison.…”
Section: Discussionmentioning
confidence: 99%
“…Non‐homologous recombination events have been reported in young allopolyploids (e.g. wheat) and may contribute to increasing genetic diversity, thus facilitating the adaptive evolution of newly formed allopolyploids (Zhang et al, 2022). A common non‐homologous recombination is homoeologous exchanges (HEs), which exchange swap pieces of DNA between subgenomes, and can lead to deletions, duplications and translocations (Mason & Wendel, 2020).…”
Section: Discussionmentioning
confidence: 99%